THE CONSTRUCTION OF THE MEANING OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN EDUCATIONAL ORGANIZATIONS: A Phenomenological Analysis of Professional Morality and the Spirituality of Teacher Service at SMP Plus Terpadu Albina, Babelan District, Bekasi Regency - Yena Herlina; Ubaid Al Faruq; Ruknan Ruknan (Yayasan Education and Social Center, 2026)
This study aims to examine the construction of meaningOrganizational Citizenship Behavior(OCB) in educational organizations through a phenomenological analysis of professional morality and spirituality of teacher devotion at Albina Integrated Plus Middle School, Babelan District, Bekasi Regency. The study used a qualitative approach with a phenomenological method to understand the life experiences (lived experience) teachers in interpreting voluntary behavior that goes beyond formal duties. Data collection was conducted through semi-structured in-depth interviews, participant observation, and documentation studies of eight informants selected using the techniquepurposive sampling. Data analysis is carried out through stagesepoche (bracketing), open coding, axial coding, And selective codingThe research results show that OCB is defined as a form of professional devotion that goes beyond formal obligations and is based on professional morality and Islamic spirituality. The values ​​of sincerity, trustworthiness,uswatun hasanah, and the orientation of blessings is the main motivation for teachers in displaying behaviorextra-rolewithout expecting material rewards. This research produced findings in the form of concepts Transcendental Professionalism, namely the understanding that OCB is influenced not only by organizational factors, but also by the moral identity and spirituality of service internalized in the school culture. These findings contribute to the development of organizational behavior theory in education and serve as a basis for strengthening an organizational culture oriented toward professionalism, collaboration, and continuous service.